2004
DOI: 10.1111/j.0013-9580.2004.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Vigabatrin Retinotoxicity in Albino Rats Depends on Light But Not GABA

Abstract: Summary:Purpose: Vigabatrin (VGB) is an irreversible inhibitor of γ -aminobutyric acid (GABA) transaminase. Its use as an antiepileptic drug (AED) has been limited because it causes retinal dysfunction, leading to visual field defects (VFDs). We performed this study to identify factors contributing to acute VGB retinotoxicity.Methods: In ex vivo experiments, Sprague-Dawley rat retinas were isolated and incubated with VGB or GABA in the presence or absence of light. In in vivo experiments, Sprague-Dawley rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…Subsequent morphological studies have described the disorganized ONL, shortened inner and outer cone segments, as well as the disrupted RGCs layer [13,14]. The VGB-elicited photoreceptor degeneration is reported to be light dependent [25,26]. However, these results are mainly harvested from histological and immunochemistry observations of fixed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent morphological studies have described the disorganized ONL, shortened inner and outer cone segments, as well as the disrupted RGCs layer [13,14]. The VGB-elicited photoreceptor degeneration is reported to be light dependent [25,26]. However, these results are mainly harvested from histological and immunochemistry observations of fixed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…One study in rodents showed that vigabatrin-associated retinopathy is associated with light exposure [72]. More recently, it has been suggested that a deficiency of taurine is implicated in the pathogenic process of vigabatrinassociated retinopathy [73,74].…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…Alterations of Müller cell morphology have been detected previously, in rabbits, during vigabatrin medication in a study by Ponjavic et al [37]. Changes in the ONL and OLM in rats on VGB medication are described by Izumi et al [40], who also suggest Müller cell dysfunction as well as photoreceptor damage as a result of exposition to VGB in combination with light, rather than as an effect of raised concentrations of GABA in the retina. In rats [39], increased GFAP immunoactivity has been interpreted as an indicator of VGB-induced Müller cell activation and gliosis formation.…”
Section: Discussionmentioning
confidence: 76%
“…Similar results are shown by Duboc et al [39], revealing ff-ERG alterations and morphological changes in Müller cells in rats. Duboc et al [39] as well as Izumi et al [40] have also shown cone photoreceptor damage in rats treated with VGB. The main goal of the present study was to further investigate the role of the drug dose in VGB-induced toxic retinopathy, functionally measured by ff-ERG.…”
Section: Introductionmentioning
confidence: 90%